Comparative Performance between Two Photogrammetric Systems and a Reference Laser Tracker Network for Large‐Volume Industrial Measurement. (4th September 2016) - Martin, Oliver C.; Robson, Stuart; Kayani, Amir; Muelaner, Jody E.; Dhokia, Vimal; Maropoulos, Paul. G.
Abstract: This paper determines the capability of two photogrammetric systems in terms of their measurement uncertainty in an industrial context. The first system – V‐STARSinca 3 from Geodetic Systems Inc. – is a commercially available measurement solution. The second system comprises an off‐the‐shelf Nikon D700 digital camera fitted with a 28 mm Nikkor lens and the research‐based Vision Measurement Software (VMS). The uncertainty estimate of these two systems is determined with reference to a calibrated constellation of points determined by a Leica AT401 laser tracker. The calibrated points have an average associated standard uncertainty of 12·4 μm, spanning a maximum distance of approximately 14·5 m. Subsequently, the two systems' uncertainty was determined. V‐STARSinca 3 had an estimated standard uncertainty of 43·1 μm, thus outperforming its manufacturer's specification; the D700/VMS combination achieved a standard uncertainty of 187 μm.